Radiation protection system referring to the regulations - Gostkowska, Bożena (Contemporary Oncology/Współczesna Onkologia, 2000)
In this paper the author provides comments on the radiation protection system in medicine, referring to the domestic and foreign regulations. She discusses some issues of the occupational and potential exposure in the context of the European Union’s regulations and also the role of the radiation protection officer during the formation of the radiation protection system in a company and its efficiency.